Koncepcje doktrynalne i wymiar praktyczny postulowanych zmian statutu organicznego województwa śląskiego w okresie II RP - Drogoń, Andrzej (Z Dziejów Prawa [czasopismo zamknięte], 2020)
After gaining independence, the Second Republic of Poland had to face many chal- lenges, among which the unification of the political system was the most important one. It deter- mined the stability of life, the homogeneity of the political system, the elimination of regional particularisms, and the construction of the basis which would unite social structure. This process faced obstacles that were frequently impossible to overcome. It was vital to reconcile contradic- tions with challenges imposed by various factors based on inner conditioning and additionally reinforced with a catastrophic economic situation, with a complex social and national condition, as well as international situation. The newly-established Silesian voivodeship was one of those regions where most of the aforementioned problems were especially pronounced. It was connected with a vast decentraliza- tion which took the form of the autonomy that was granted to this voivodeship. The present article discusses only a handful of examples that depict the conflicts which in practical terms manifested the differences concerning the extent of autonomous rights that had been attributed to the Silesian voivodeship. At that time, the conflicts were not accompanied by the doctrinal debate nor by any other legal discussion on the matter in question that would specify mutual relations between the central government units and the autonomous authorities, mainly the Silesian Sejm. The problem of the autonomy of the Silesian Voivodeship and the constitutionality of the or- ganic statute became the subject of a serious doctrinal discussion after the adoption of the April constitution in 1935. The changes that had been introduced had a considerable influence on some political solutions of the Silesian voivodeship. This direction seemed to confirm the thesis about the inevitability of serious changes in the political structure of this voivodeship. The adoption of one of the two solutions, namely either the abolishment of the political system that guaranteed autonomy or its deep reconstruction, was just a matter of time.